2017
DOI: 10.30544/297
|View full text |Cite
|
Sign up to set email alerts
|

Integrated procedure for recycling and valorization of useful components from secondary raw materials based on hard metals

Abstract: Wide application of hard metals requires increased consumption of their constituents. Their high cost and scarcity impose the need for finding new, both ecologically and economically justified ways for their production. In presented research, on the basis of previous research, a review of an integrated technological procedure of recycling and valorization of useful components from hard metals secondary raw materials is given.Integrated procedure for processing of hard metal's waste enables the preparation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…This process reduces the need for natural raw materials, saves energy in production, and reduces environmental pollution. Numerous studies have reported that the waste from different industrial processes can be utilized successfully in the fabrication of new valuable materials [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This process reduces the need for natural raw materials, saves energy in production, and reduces environmental pollution. Numerous studies have reported that the waste from different industrial processes can be utilized successfully in the fabrication of new valuable materials [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%